Manajemen Konflik; Evaluasi Kine Effect Of Conflict Management And Performance Evaluation On Human Resource Development At Indomaret In Walmas (BIMA Journal (Business, Management, & Accounting Journal), 2025)
This study aims to analyze the influence of conflict management and performance evaluation on human resource development in Indomaret in Walenrang Lamasi in 2024. The research method uses quantitative methods. The data research analysis used was multiple linear regression analysis. This study was conducted with 46 respondents with results showing an R2 value of 0.543 and a simultaneous significance of p